THE EFFECT OF HUMAN RESOURCE COMPETENCY TRAINING AND ADMINISTRATIVE SYSTEM FOR PHARMACEUTICAL PERSONNEL CAPABILITY IMPROVEMENT AT UDB MEDIKA PHARMACY - Listyani, Tiara Ajeng; Listyorini, Puguh Ika; Akhmad, Khabib Alia; Oktaviana, Aptika (LPPM Universitas Duta Bangsa Surakarta, 2023)
UDB Medika Pharmacy is a new form of business that was established to increase the income generating of Duta Bangsa University, Surakarta. The lack of experience of Pharmacy Staff at the UDB Medika Pharmacy as practitioners in the pharmacy sector creating human resources in UDB Medika pharmacies requires real training in carrying out pharmaceutical service standards in pharmacies. This study aims to assess the level of knowledge and ability of pharmacy staff, and to find out whether there is a significant influence before and after the Human Resources Competency and Administration System training for pharmacists at UDB Medika Pharmacy. This study was a pre-experimental study with a one-group design that was given a pre-test and a post-test. The results of this study indicate that the average score after training is 78.51, which is higher than the score before training, which is 52.58. Competency Training on Human Resources and Administrative Systems for pharmacists at UDB Medika Pharmacy has been proven to be able to increase the knowledge and skills of pharmaceutical staff at UDB Medika pharmacies in providing pharmaceutical services in accordance with pharmacy service standards at pharmacies, assessed from test results before and after training.